Engaging Users on Social Media Business Pages: The Roles of User Comments and Firm Responses - Cheng, Xiaoye; Bala, Hillol; Yang, Mochen (MIS Quarterly, 2024)
Firms must strategically manage their responses to user comments to keep users engaged on their social media business pages. The question of whether, how, and when a firm should respond to user comments to achieve favorable outcomes is of great interest to researchers and practitioners. We focus on these questions and study the effects of initial user comments and firm responses on subsequent user engagement on social media business pages. In particular, we theorize and examine how two features of initial user comments (i.e., sentiment and controversialness) and two features of firm responses (i.e., uniqueness and timeliness) jointly affect the volume and sentiment of subsequent user comments. By analyzing data from the Facebook business pages of multiple U.S. retailers (10,312 firm posts from 37 firms and over 1 million user comments), we found that firms are more likely to respond to negative comments (than positive or neutral comments) but less likely to respond to controversial comments (which evoke diverse opinions and emotions). Further, we found that engaging with negative and controversial comments and promptly responding to comments are linked to an increase in the volume of subsequent user comments but also to a more negative sentiment in these comments. We also found that providing unique responses improves the volume and sentiment of subsequent user comments. Our findings offer theoretical and practical insights into firms’ response management on social media.